Role of intralesional bleomycin and intralesional triamcinolone therapy in residual haemangioma following propranolol. Issue 7 (July 2018) - Pandey, V.; Tiwari, P.; Sharma, S.P.; Kumar, R.; Singh, O.P.
Abstract: With the emergence of propranolol as the first choice of treatment for problematic infantile haemangioma at many centres, the number of patients with a partial or non-response to propranolol has also been growing. This study investigated the role of intralesional bleomycin and triamcinolone in patients with residual disease following propranolol therapy for infantile haemangioma. Sixty-seven patients with residual haemangioma were assigned randomly to receive either intralesional bleomycin (group A, n  = 36) or intralesional triamcinolone (group B, n  = 31). The response to treatment and adverse effects were assessed in both groups. All patients received at least four doses and a maximum of six doses of the assigned drug. In group A (mean follow-up 9.38 months), 47.2% had an excellent response and 44.4% a good response. In group B (mean follow-up 7.42 months), 25.8% had an excellent response and 48.4% a good response. There was no difference in overall response between the groups ( P  = 0.074). Among patients who were initially non-responders to propranolol, bleomycin showed a better response than triamcinolone ( P  = 0.037). This may be due to an overlap in the mechanism of action of propranolol and triamcinolone. Thus, intralesional bleomycin should be preferred in patients with no initial response to propranolol therapy, while bleomycin or triamcinolone can be used in patients with a partial response to propranolol therapy, as they have equal efficacy.